Influence of circadian rhythm on the determination of the IMMune Age indeX (IMMAX) - Trebing, Sina; Bröde, Peter; Claus, Maren; Watzl, Carsten (Frontiers in Aging, 2025)
IntroductionTo study the impact of immunosenescence on various biological processes the determination of the immune age has gained much interest in recent years. Based on easily determined five immune cell components we recently developed the IMMune Age indeX (IMMAX) as a biomarker for immunosenescence. However, the influence of the circadian rhythm of immune cell concentrations in peripheral blood on the determination of the IMMAX was unclear.MethodsTherefore, we conducted an experimental study with 50 participants aged 20–69 years and took blood samples at 8 a.m., 1 p.m. and 6 p.m. to determine the IMMAX over the day. Additionally, the chronotype of the study participants was assessed by D-MEQ questionnaire.ResultsWhile individual immune cell ratios showed changes during the day, we determined no significant variability of the IMMAX score between the measurements. Interestingly, the individual chronotype influenced the diurnal rhythm of the IMMAX score with morning types showing a decrease of IMMAX values during the day.ConclusionThis longitudinal trial strengthens the IMMAX as a robust biomarker for the immune age independent from time of blood sampling.